Sampled-data velocity-free consensus of Multiple Euler-Lagrange systems under irregular communication delays - Yilin Wang; Jiahao Dai; Pengfei Zhang (PLoS ONE, 2025)
This paper addresses the challenging problem of achieving sampled-data, velocity-free consensus for multiple Euler-Lagrange systems under irregular communication delays. While passivity-based control (PBC) is a powerful framework for such systems, existing works fundamentally require continuous feedback from neighbors, as their stability proofs cannot handle the discontinuous right-hand-side dynamics generated by sampled-data and abrupt delays. This limitation renders conventional PBC methods inapplicable in many realistic networked scenarios. This work bridges that theoretical gap by introducing a novel control and analysis method. Our strategy treats the system dynamics over continuous intervals separately from the discrete instants of discontinuity, allowing us to rigorously prove consensus. The control strategy incorporates a virtual system framework to operate without velocity measurements and successfully relaxes the impractical requirement that delays must have finite derivatives. Finally, simulation examples are provided to demonstrate the effectiveness of the proposed consensus algorithm. Index terms: Euler-Lagrange system, Multi-agent system, Sampled-data control.